Friction in MASYUMI: A Historical Studies on Internal Conflict Event of Islamic Party in Indonesia, 1945-1960 - Hidayat, Asep Achmad; Gumilar, Setia (ASPENSI in Bandung, Indonesia, 2016)
ABSTRACT: As one of the modern Islamic organizations, MASYUMI (Majelis Syuro Muslimin Indonesia or Council of Indonesian Muslim Association), in its development, cannot be separated from the internal dynamics. The dynamics influenced toward the pattern of the struggle that it did. The differences of MASYUMIâs characteristics are the main reasons for the friction. Besides, internal political interests became the other causes of MASYUMIâs discordance. Different characters and their political interests led to the domination of one group in MASYUMI. The political domination impacts on the integrity of the members in it. This study tries to elaborate of friction in MASYUMI as modern political party in Indonesia, since 1940s to 1960s in Indonesian political landscape. The method of study is a qualitative research, especially historical method, in which the Heuristic, Critics, Analysis, and Historiography are the steps in historical research. The findings show that as a result of these frictions in MASYUMI, the authority and dignity of the organization has decreased. MASYUMI was no longer become covered Islamic organizations, as well as on the initial formation. Many Muslims did not want to join again with MASYUMI. Inequalities in the management of distributing the resources unevenly became the early setback that MASYUMI up cannot be glimpsed again by Muslims, either personally or collectively. KEY WORDS: Modern Islamic Party; Internal Conflict; Domination; Political Interests; Indonesian Political Landscape.Â Â About the Authors: Dr. Asep Achmad Hidayat and Dr. Setia Gumilar are the Lecturers at the Faculty of Adab and Humanities UIN SGD (State Islamic University, Sunan Gunung Djati) Bandung, Jalan A.H. Nasution No.105 Cipadung, Bandung 40614, West Java, Indonesia. E-mail address is: gumilarsetia@yahoo.comHow to cite this article? Hidayat, Asep Achmad & Setia Gumilar. (2016). âFriction inÂ MASYUMI: A Historical Studies on Internal Conflict Event of Islamic Party in Indonesia, 1945-1960â in TAWARIKH: International Journal for Historical Studies, Vol.8(1) October, pp.59-68. Bandung, Indonesia: Minda Masagi Press and UIN SGD Bandung, ISSN 2085-0980. Chronicle of the article: Accepted (September 8, 2016); Revised (October 5, 2016); and Published (October 28, 2016).